Selection of Contraceptive Methods for Postpartum Mothers Using Balanced Counseling Strategies - Ramadiyanti, Aliya; Sofiyanti, Santi (Universitas Ibn Khaldun Bogor, 2025)
One of the problems that occurs in the national family planning program in Indonesia is the low absorption of MKJP. A balanced consultation strategy is part of an effort to improve MKJP. The purpose of this study was to examine the choice of contraceptive methods for postpartum mothers related to the use of SKB-KB at the Ibrahim Adjie Health Center. Ibrahim Adjie Health Center was the location of the study in March–April 2023, which used a retrospective cohort design. A total of 81 postpartum mothers were sampled, selected using the simple random sampling technique. For this data set, we used the chi- square test and the SPSS T test. Although the bivariate analysis did not find a correlation between the application of SKB-KB and the choice of method (p = 0.167), the analysis of the relationship between the choice of method and husband's support showed a correlation (p = 0.001), which indicated a significant relationship. The SKB given to postpartum mothers aims to improve understanding and selection of contraceptive methods according to needs, especially for long-term methods. This counseling method will provide the expected results if it is also given to husbands to improve their understanding of contraceptives.